2018
DOI: 10.1029/2018rs006537
|View full text |Cite
|
Sign up to set email alerts
|

I 21‐cm Cosmology and the Bispectrum: Closure Diagnostics in Massively Redundant Interferometric Arrays

Abstract: New, massively redundant low‐frequency arrays allow for a novel investigation of closure relations in interferometry. We employ commissioning data from the Hydrogen Epoch of Reionization Array to investigate closure quantities in this densely packed grid array of 14‐m antennas operating at 100 to 200 MHz. We investigate techniques that utilize closure phase spectra for redundant triads to estimate departures from redundancy for redundant baseline visibilities. We find a median absolute deviation from redundanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 70 publications
3
42
0
Order By: Relevance
“…This result is consistent with other metrics of non-redundancy, e.g. closure phase (Carilli et al 2018). Likewise, this is consistent with the rough level of non-redundancy seen in the fiducial simulations of Orosz et al (2019), which take as inputs to their parameterized non-redundancy the construction tolerances of HERA dish and feed positioning.…”
Section: Fractional Non-redundancysupporting
confidence: 88%
“…This result is consistent with other metrics of non-redundancy, e.g. closure phase (Carilli et al 2018). Likewise, this is consistent with the rough level of non-redundancy seen in the fiducial simulations of Orosz et al (2019), which take as inputs to their parameterized non-redundancy the construction tolerances of HERA dish and feed positioning.…”
Section: Fractional Non-redundancysupporting
confidence: 88%
“…Similar to how unmodeled diffuse emission created gain errors in sky calibration, these kinds of non-redundancies will create errors in redundant calibration and will appear at similar delays (Orosz et al 2019). Previous work showed that non-redundancy seems to be worse for short baselines (Carilli et al 2018), but quantifying this in more detail is still in progress (Dillon et al in prep.). The AR calibration gains also show significant power at τ 800 ns, which shows that redundant calibration is not immune to picking up cross coupling instrumental systematics.…”
Section: Of Equation 5 Asmentioning
confidence: 99%
“…We choose low, fiducial, and high error levels for each nonredundancy type, which we list in Table 1. These were chosen to represent realistic 4 antenna-to-antenna variations (Carilli et al 2018), with the condition that the resulting errors in visibilities are comparable for sources of non-redundancy at the same error level. To verify this, we show in Figure 2 the standard deviation of all the nominally redundant measurements of a single unique 14.6 m baseline.…”
Section: Visibility Simulation With Non-redundancymentioning
confidence: 99%